Il mutamento signorile. Assetti di potere e comunicazione politica nelle campagne dell'Italia centro-settentrionale (1080-1130 c.) - FIORE, Alessio (Reti Medievali E-Book, 2017)
The purpose of this book is to explore the transformations in the functioning of power in the countryside of the kingdom of Italy over the fifty years at the turn of the 1100s, and more particularly the process of affirmation and crystallization of the rural lordship. The investigation develops through the reconstruction not only of the structures of power over men and space, and of the related social morphologies, but also of the political communication system at the local level. The outbreak of the civil wars connected with the "struggle for the Investitures", after 1080, translates into a clear reconfiguration of the socio-political matrix, transforming both the practices of local power, and the instruments of political communication and the related documentation. The Italian case offers in this sense a new perspective on the great and still open historiographic problem, of the "feudal revolution" in the European context.